2020
DOI: 10.11646/zootaxa.4885.4.3
|View full text |Cite
|
Sign up to set email alerts
|

A New Species of Mud Turtle of Genus Kinosternon (Testudines: Kinosternidae) from the Pacific Coastal Plain of Northwestern Mexico

Abstract: We describe a new species of mud turtle of the genus Kinosternon from the Pacific Coastal Plain of the Mexican states Sinaloa and Nayarit. The new species shares morphological characters with the recently described Kinosternon vogti, which are unique to these two turtles and separate them from the other species of the genus. The new species differs from K. vogti by skin coloration, size, and the scutellation of both carapace and plastron. We also present a molecular phylogeny of the family Kinosternidae based … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
6
0
2

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 962 publications
(8 citation statements)
references
References 21 publications
0
6
0
2
Order By: Relevance
“…remarkable amounts of morphological crypsis, with numerous novel species being described recently (e.g. Scott et al 2018, Loc-Barragán et al 2020. Differences between and among dispersed populations in characters as important as egg size therefore may be indicative of more substantial underlying biological differences.…”
Section: Discussionmentioning
confidence: 99%
“…remarkable amounts of morphological crypsis, with numerous novel species being described recently (e.g. Scott et al 2018, Loc-Barragán et al 2020. Differences between and among dispersed populations in characters as important as egg size therefore may be indicative of more substantial underlying biological differences.…”
Section: Discussionmentioning
confidence: 99%
“…One additional relevant article on plastic ingestion by a freshwater turtle was brought to our attention by colleagues. We recognize 359 extant turtle species globally of which seven are sea turtles 21 , 26 28 , while acknowledging that taxonomy in this group remains fluid.…”
Section: Methodsmentioning
confidence: 99%
“…Twenty-five species have been described within the genus but its taxonomy remains controversial, with new species being described as recently as 2020. The species Kinosternon cora was described recently in The Pacific Coastal plain of northwestern Mexico (Loc-Barragań et al, 2020) and the species Kinosternon vogti was described in 2018 in Jalisco, Mexico (Loṕez-Luna et al, 2018).…”
Section: Introductionmentioning
confidence: 99%
“…Amplicons were purified using magnetic beads and sequenced in both forward and reverse direction on an ABI3500 at Universidad de los Andes (Colombia). We chose to work with this nuclear region (R35) because previous studies have shown them to be useful in resolving deep relationships in turtle phylogenetics (Fujita et al, 2004;Loc-Barragań et al, 2020).…”
Section: Intron 1 Of the Fingerprint Protein 35 (R35) Genementioning
confidence: 99%